Contrastive analysis of Mafalda’s translations in French by Jacques and Anne-Marie Meunier - Munguía González, Carolina (2020)
Mafalda's comic strips have transcended linguistic and cultural barriers even in the least expected regions from all over the world, such was its influence that a couple of years after it was published this character was chosen to host the Declarations of the Rights of the Child campaign for Unicef. Despite the popularity of the comic, research work and analysis about its several translations is scant. This article addresses a contrastive analysis done to the first volume of Mafalda (1966) and its French counterpart trans- lated by Jacques and Anne-Marie Meunier, Mafalda et ses amis (1984) two decades later; emphasizing, particularly, on the cultural elements of both languages and identifying the difficulties of the translation, sociocultural and linguistic, using a qualitative meth- odology of data interpretation; evidencing that even though the Meunier's translations merit recognition due to their ability to transfer some of the cultural and humorous ele- ments into new authentic content meaningful to the target audience, these translations loose to some extent some of the elements that characterizes the comic.